A versatile continuous model for predicting various post-peak patterns of FRP-confined concrete. (15th August 2022) - Zhu, Zhongfeng; Zhou, Yingwu; Li, Zongjun; Li, Haixiang; Hu, Biao; Li, Pengda
Highlights: A continuous and integrable model is capable of describing all the post-peak patterns associated with diverse types of FRPs confined concrete. The most comprehensive database to date, covering all categories of post-peak behaviours and types of FRPs. The values of a strain efficiency factor for different types of FRPs have been determined. The performance of some existing strength and strain models is evaluated. Abstract: The utilization of fiber reinforced polymers (FRPs) is currently recognized as an effective solution against concrete deterioration. The external FRP not only provides strength and durability to the concrete structure but also propels the improvement of the internal concrete performance due to the confinement effect. To accurately predict the true response of the concrete core represented in various patterns caused by the confinement effect, a versatile continuous model is inevitable for analyzing the mechanical performance of confined concrete. To achieve this, in the present study, a comprehensive database has been established and reviewed. The confinement mechanisms and four post-peak patterns in terms of stress–strain relationship to the intensification of confinement effect are summarized. The ultimate state predictions and the mathematical expressions of stress–strain models are evaluated. Accordingly, the strain efficiency factors of different types of FRPs, and the methodology for four major coefficient parameters have been proposed to develop a versatile continuous model for FRP-confined concrete. Notably, the proposed model is a derivable, and integrable single-segment expression, which is capable of describing all the post-peak patterns associated with different types of FRPs.